Which Patients Are Most Likely to Benefit From Total Joint Arthroplasty?. Issue 5 (23rd April 2013) - Hawker, Gillian A.; Badley, Elizabeth M.; Borkhoff, Cornelia M.; Croxford, Ruth; Davis, Aileen M.; Dunn, Sheila; Gignac, Monique A.; Jaglal, Susan B.; Kreder, Hans J.; Sale, Joanna E. M.
Abstract: Objective: To evaluate patient predictors of good outcome following total joint arthroplasty (TJA). Methods: A population cohort with hip/knee arthritis (osteoarthritis [OA] or inflammatory arthritis) ages ≥55 years was recruited between 1996 and 1998 (baseline) and assessed annually for demographics, troublesome joints, health status, and overall hip/knee arthritis severity using the Western Ontario and McMaster Universities OA Index (WOMAC). Survey data were linked with administrative databases to identify primary TJAs. Good outcome was defined as an improvement in WOMAC summary score greater than or equal to the minimal important difference (MID; 0.5 SD of the mean change). Logistic regression and Akaike's information criterion were used to determine the optimal number of predictors and the best model of that size. Log Poisson regression was used to determine the relative risk (RR) for a good outcome. Results: Primary TJA was performed in 202 patients (mean age 71.0 years; 79.7% female; 82.7% with >1 troublesome hip/knee; 65.8% knee replacements). Mean improvement in WOMAC summary score was 10.2 points (SD 18.05; MID 9 points). Of these patients, 53.5% experienced a good outcome. Four predictors were optimal. The best 4‐variable model included pre‐TJA WOMAC, comorbidity, number of troublesome hips/knees, and arthritis type (C statistic 0.80). The probability of a good outcome was greater with worse (higher) pre‐TJA WOMAC summary scores (adjusted RR 1.32 per 10‐point increase; P < 0.0001), fewer troublesome hips/knees (adjusted RR 0.82 per joint; P = 0.002), OA (adjusted RR for rheumatoid arthritis versus OA 0.33; P = 0.009), and fewer comorbidities (adjusted RR per condition 0.88; P = 0.01). Conclusion: In an OA cohort with a high prevalence of multiple troublesome joints and comorbidity, only half achieved a good TJA outcome, defined as improved pain and disability. A more comprehensive assessment of the benefits and risks of TJA is warranted.